A Novel DNA Vaccine Against SARS-CoV-2 Encoding a Chimeric Protein of Its Receptor-Binding Domain (RBD) Fused to the Amino-Terminal Region of Hepatitis B Virus preS1 With a W4P Mutation - Jeong, Hyein; Choi, Yu-Min; Seo, Hyejun; Kim, Bum-Joon (Frontiers in Immunology, 2021)
A coronavirus SARS-CoV-2, which has caused the pandemic viral pneumonia disease COVID-19, significantly threatens global public health, highlighting the need to develop effective and safe vaccines against its infection. In this study, we developed a novel DNA vaccine candidate against SARS-CoV-2 by expressing a chimeric protein of its receptor-binding domain (RBD) fused to a 33-bp sequence (11 aa) from the hepatitis B virus (HBV) preS1 region with a W4P mutation (W4P-RBD) at the N-terminal region and evaluated its immunogenicity. In vitro transfection experiments in multiple cell lines demonstrated that W4P-RBD vs. wild-type RBD protein (W-RBD) led to enhanced production of IL-6 and TNFα at the transcription and translation levels, suggesting the adjuvant potential of N-terminal HBV preS1 sequences for DNA vaccines against SARS-CoV-2. W4P-RBD also led to enhanced production of IgG and IgA, which can neutralize and block SARS-CoV-2 infection in both blood sera and bronchoalveolar lavage (BAL) fluid from the lung in vaccinated mice. Additionally, W4P-RBD led to an enhanced T-cell-mediated cellular immune response under S1 protein stimulation. In summary, W4P-RBD led to robust humoral and cell-mediated immune responses against SARS-CoV-2 in vaccinated mice, highlighting its feasibility as a novel DNA vaccine to protect against SARS-CoV-2 infection.